Strategi Pembelajaran Bahasa Inggris untuk Mahasiswa Farmasi: Pendekatan Interdisipliner - Mariana Mariana; Rudi Purwana (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to explore and develop effective English language teaching strategies for pharmacy students through an interdisciplinary approach. In the context of globalization and advancements in health technology, the ability to communicate in English is crucial for pharmacy professionals. The research methodology employed combines both qualitative and quantitative approaches. Data were collected through in-depth interviews, surveys, and observations at several higher education institutions offering pharmacy programs. The findings indicate that integrating pharmacy content with English language teaching can enhance students' understanding of medical terminology and their ability to communicate professionally. Effective strategies include the use of case-based learning materials, clinical simulations, and collaboration with faculties of pharmacy and language. Additionally, the use of digital technology, such as learning apps and online platforms, was found to enrich the students' learning experience. The study concludes that an interdisciplinary approach in teaching English to pharmacy students not only improves language competence but also prepares them for future professional challenges. Recommendations for the implementation of these strategies in higher education settings are provided in this study.